1998
DOI: 10.1164/ajrccm.157.6.9712007
|View full text |Cite
|
Sign up to set email alerts
|

Adherence with Twice-daily Dosing of Inhaled Steroids

Abstract: Poor adherence to medication regimens may be contributing to the recent increase in asthma morbidity and mortality. We examined patient characteristics that may influence adherence to twice-daily inhaled steroid regimens. Fifty adults with moderate to severe asthma completed questionnaires examining sociodemographics, asthma severity, and health locus of control. Adherence was electronically monitored for 42 d. Following monitoring, patients' understanding of asthma pathophysiology and the function of inhaled … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

13
204
4
7

Year Published

2002
2002
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 362 publications
(228 citation statements)
references
References 28 publications
13
204
4
7
Order By: Relevance
“…‡ Adjusted for all the variables shown plus the external factors, which include variables for socioeconomic status (i.e., household income, wealth [home ownership and home value], and highest level of education for the head of household); barriers to receiving care (i.e., variables for clinic not open at times needed, difficulty in getting to physician's office, couldn't get a timely appointment, long clinic wait to see physician, and couldn't afford clinical visit) (25); barriers to obtaining medication (i.e., variables representing co-payment amount and patient-reported difficulty affording medication); patient-clinician communication (21); level of social support and stressors (e.g., from family, friends, neighbors, etc.) (26); perceived discrimination (27); and exposure to crime and/or violence (28).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…‡ Adjusted for all the variables shown plus the external factors, which include variables for socioeconomic status (i.e., household income, wealth [home ownership and home value], and highest level of education for the head of household); barriers to receiving care (i.e., variables for clinic not open at times needed, difficulty in getting to physician's office, couldn't get a timely appointment, long clinic wait to see physician, and couldn't afford clinical visit) (25); barriers to obtaining medication (i.e., variables representing co-payment amount and patient-reported difficulty affording medication); patient-clinician communication (21); level of social support and stressors (e.g., from family, friends, neighbors, etc.) (26); perceived discrimination (27); and exposure to crime and/or violence (28).…”
Section: Discussionmentioning
confidence: 99%
“…For internal factors, we further subdivided our variables into the following categories: measures related to perception (18) and knowledge (19) about disease; beliefs (i.e., necessity and concern) about (20), knowledge of (21), and past experience with controller medication; the perceived locus of control over asthma, such as internal, chance, powerful others, and god (22,23); self-efficacy (14); readiness to change (14); depression (24); and the personal importance of physician trust. Past experience with controller medications and the personal importance of physician approval were not previously validated metrics.…”
Section: Survey Administration and Designmentioning
confidence: 99%
See 1 more Smart Citation
“…6 However, little is known about the relationship between provider-patient communication during pediatric asthma visits and its association with child-and caregiver-reported control medication adherence. 7,8 Apter et al 7 found that poor patient ratings of patient-provider communication about asthma were related to poor adherence to inhaled steroids. Chambers et al 8 discovered that regular inhaled corticosteroid use was related to whether patients perceived themselves as actively involved in treatment decisions during medical visits.…”
mentioning
confidence: 99%
“…A limitation of these previous studies is that they relied on subjective patient reports of medical visit communication rather than objective data, such as audio-tape recordings of the visits. 7,8 Our previous work demonstrated that providers rarely asked for child or caregiver input into the child' s asthma treatment plan during audio-taped pediatric medical visits. 9 This current article examines how certain aspects of provider-patient communication that are recommended by the national asthma guidelines (ie, number of control medication questions the provider asks, the total number of medication questions asked by children, and the provider asking for child and caregiver input into the asthma treatment plan) are associated with child asthma medication adherence 1 month after the audio-taped visit.…”
mentioning
confidence: 99%